Hierarchical Co(OH)F/CoFe-LDH heterojunction enabling high-performance overall water-splitting. Issue 34 (10th August 2022) - Qin, Mingliang; Wang, Yamei; Zhang, Huaming; Humayun, Muhammad; Xu, Xuefei; Fu, Yanjun; Kadirov, Marsil K.; Wang, Chundong
Abstract : Due to the serious energy and environmental issues, hydrogen generation via water splitting has been regarded as a green and promising alternative strategy to the use of fossil fuels. Abstract : Due to the serious energy and environmental issues, hydrogen generation via water splitting has been regarded as a green and promising alternative strategy to the use of fossil fuels. Developing highly efficient and non-noble metal based dual-functional electrocatalysts for overall water splitting to generate hydrogen and oxygen has become more critical. In order to fulfill the requirements of efficient hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), herein, we report novel hierarchical Co(OH)F@CoFe-LDH heterostructured nanorod arrays fabricated via a facile two-step approach. The resultant Co(OH)F@CoFe-LDH displays exceptional electrocatalytic OER and HER activity with a small overpotential of 240 mV and 130 mV at 10 mA cm −2, respectively. Further, the electrocatalyst revealed excellent long-term stability during a recyclability test for 37 h. The superior performance of Co(OH)F@CoFe-LDH can be attributed to the synergistic effect at the interface of the Co(OH)F nanorods and the covered CoFe-LDH nanosheets. Meanwhile, Co(OH)F@CoFe-LDH as a water electrolyzer to produce a current density of 10 mA cm −2 requires a small voltage of 1.58 V. This work paves the way for the design and construction of low cost and highly efficient 3D hierarchical electrodes for practical applications in electrocatalysis.